Water Security in the Mekong River and Regional Stability in Southeast Asia - Ribka, Michelle (President University, 2017)
One of the main issues in international relations today is about the security of (natural) resources. Water is now increasingly viewed as one of strategic resource that has to be secured. In this context, water security and international relations are often intertwined. It can lead to either interstate cooperation and even conflict. This paper discusses the importance of water management in the Mekong river. This river flows from China, to Myanmar, Thailand, Laos, Cambodia and ends in Vietnam. Mekong river is also one of the world’s greatest and resource rivers. This paper argues that the water security management in the Mekong River is not only crucial for the above countries but it is also playing a very significant role in the regional stability in Southeast Asia.